Leucogranite Records Multiple Collisional Orogenies - Li Liu; Di‐Cheng Zhu; Qing Wang; Peter A. Cawood; Daniel F. Stockli; Lisa D. Stockli; Chao Lin; Jin‐Jiang Zhang; Liang‐Liang Zhang; Zhi‐Dan Zhao (Geophysical Research Letters)
Abstract The geological evolution of orogens is the sum of events related to both their cycle of generation as well as features inherited from their basement units. The Himalayan Orogen provides a well‐constrained Cenozoic history of active plate convergence and orogenic processes overprinting an early Paleozoic orogen. A total of 1,627 Himalayan leucogranite zircons were depth‐profiled showing high resolution (0.6 μm) internal age structures. Zircon rim ages record a detailed and complex history of melting and deformation, postdating the North Indo‐Australie Orogen (ca. 490–460 Ma) documented by the zircon core age data. An interesting finding is the inconsistency of age groups between detrital zircons in the Himalaya and inherited cores of leucogranite zircons, re‐evaluating the argument that leucogranites are purely derived from melting of metasedimentary rocks. Variations in the thickness of zircon rims corresponds with changing Cenozoic orogenic stages with rims thicker than 4 μm indicating the extensional regime.